Mechanism of inert inflammation in an immune checkpoint blockade-resistant tumor subtype bearing transcription elongation defects - Vishnu Modur; Belal Muhammad; Jun-Qi Yang; Yi Zheng; Kakajan Komurov; Fukun Guo (Cell Reports, 2023)
Summary: The clinical response to immune checkpoint blockade (ICB) correlates with tumor-infiltrating cytolytic T lymphocytes (CTLs) prior to treatment. However, many of these inflamed tumors resist ICB through unknown mechanisms. We show that tumors with transcription elongation deficiencies (TEdef+), which we previously reported as being resistant to ICB in mouse models and the clinic, have high baseline CTLs. We show that high baseline CTLs in TEdef+ tumors result from aberrant activation of the nucleic acid sensing-TBK1-CCL5/CXCL9 signaling cascade, which results in an immunosuppressive microenvironment with elevated regulatory T cells and exhausted CTLs. ICB therapy of TEdef+ tumors fail to increase CTL infiltration and suppress tumor growth in both experimental and clinical settings, suggesting that TEdef+, along with surrogate markers of tumor immunogenicity such as tumor mutational burden and CTLs, should be considered in the decision process for patient immunotherapy indication.